2015
DOI: 10.1039/c5ra02092a
|View full text |Cite
|
Sign up to set email alerts
|

Study of the structural, thermal, optical, electrical and nanomechanical properties of sputtered vanadium oxide smart thin films

Abstract: Vanadium oxide thin films were grown on both quartz and Si(111) substrates utilizing pulsed RF magnetron sputtering technique at room temperature with RF power at 100 W to 700 W. The corresponding thicknesses of the films were increased from 27.5 nm to 243 nm and 21 nm to 211 nm as RF power increased from 100 W to 700 W for quartz and silicon substrates, respectively. X-ray diffraction and field emission scanning electron microscopy were carried out to investigate the phase and surface morphology of the deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
32
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 55 publications
(68 reference statements)
12
32
4
Order By: Relevance
“…However, in the present study, no other V species was found except V 4+ and V 5+ . The percentage of V 5+ was found as major phase e.g., about 75-80% [9]. The presence of minor VO 2 phase is not detected in XRD analysis possibly due to the dominated amorphous nature of the deposited film.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…However, in the present study, no other V species was found except V 4+ and V 5+ . The percentage of V 5+ was found as major phase e.g., about 75-80% [9]. The presence of minor VO 2 phase is not detected in XRD analysis possibly due to the dominated amorphous nature of the deposited film.…”
Section: Resultsmentioning
confidence: 92%
“…oxide states of vanadium (except V 7 O 13 ), shows smart transition behaviour as a function of temperature or voltage. However, smart or reversible phase transition of V 2 O 5 is still debatable issue [10] though the reversible phase transitions of V 2 O 5 thin films/layers are experimentally observed by three groups [9,11,12] including the present authors [9].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Some studies have been described the films characterization with a thickness greater than 160 nm, but do not refer to the material crystalline structure study and its dependence on the thickness (KRISHNA; BHATTACHARYA, 1997).Others studies have been described the crystalline structure and the thickness effects on the optical properties only in films with thickness above 110 nm (RAMANA; SMITH; HUSSAIN, 2003;SINGH;KAUR, 2008;Zhang;Zuo;Lu, 2017) and another the influence of the sputtering power on the optical, electrical and nanomechanical properties for films (Porwal et al, 2015). Thus, no study was found relating the thickness and microstructure of films deposited by thermal evaporation with the optical absorption band.…”
Section: Introductionmentioning
confidence: 99%